Roadwork construction / Muhammad Azwan Arash Wan Salman - Wan Salman, Muhammad Azwan Arash (Universiti Teknologi MARA, Perak, 2019)
As part of future improvement, road is very important for vehicle to connect each one and another from place to place. Therefore, this report will discuss about roadwork construction for the future development of commercial building and residential building at the surrounding of the construction. The aim for this study is to observe the sequence of road construction in the project. The objective of this report is to determine the factors should be considered in roadwork construction consist of material and machineries to be used during the layer of pavement and from the ground level.